Fatigue crack growth resistance and crack closure behavior in two aluminum alloys for aeronautical applications - Rodrigues,Elenice Maria (2005)
Aluminum-lithium alloys are candidate materials for many aerospace applications because of their high specific strength and elastic modulus. These alloys have several unique characteristics such as excellent fatigue crack growth resistance when compared with that of the conventional 2000 and 7000 series alloys. In this study, fatigue crack propagation behavior has been examined in a commercial thin plate of Al-Li-Cu-Mg alloy (8090), with specific emphasis at the fatigue threshold. The results are compared with those of the traditional Al-Cu-Mg alloy (2024). Fatigue crack closure is used to explain the different behavior of the compared alloys.